How Mediatization Of Arabic Learning Affects Religious Culture At The Indonesian Islamic University - Nur Ali; Muassomah Muassomah; Nursyirwan Nursyirwan; Mufliha Wijayati (Ijaz Arabi Journal of Arabic Learning, 2022)
Mediatization has transformed Arabic-language education from the personal to the instrumental and has provided a rapid, convergent approach to language learning. Such an approach, however, has distanced students from their education, as mediatized learning cannot convey the teacher's values. This article seeks not only to map the changing trends in Arabic-language education but also to analyze the implications of the ongoing mediatization process. Students' literacy influences their ability to learn Arabic through self-motivated, self-regulated learning and affects religious culture. This study finds that language learning has been transformed from a personal-religious cultural approach to an instrumental-functional one. At the same time, students have become dependent on technology and lost religious values, while their language has become formalized owing to the standardization of learning media. This study recommends improving media literacy to maximize students' achievements and free them from their dependence on media technology.